The Accounting Dimension of Banking Services and its Impact on Sustainable Development (An Applied Study in One of The Branches of Rafidain Bank) - Sebti, Zina Mohammed; Majeed, Hashim Jabbar; Madhi , Maydia Hassan (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
Abstract: Solar chimney power plants (SCPPs) are increasingly recognized as a viable renewable energy solution in hot and arid regions. This study investigates how different chimney diameter ratios affect the performance of a solar chimney power plant using computational fluid dynamics (CFD). A 2D steady-state CFD analysis was conducted in ANSYS Fluent. The model used a constant chimney height of 30 m and a collector radius of 20 m. Chimney diameter ratios of 0.03, 0.05, and 0.1 were tested. The k-omega turbulence model with the Boussinesq approximation was used to simulate buoyancy-driven airflow. Results show that smaller chimney diameters lead to higher air velocities and increased turbulence kinetic energy, enhancing output power. Optimal airflow and performance were observed when the chimney diameter ratio was set to 0.03. This study provides a focused comparative CFD analysis on the effect of diameter variation alone while other design parameters remain fixed. The findings offer engineering insights for optimizing the geometry of SCPPs, particularly for application in regions such as Baghdad with high solar radiation.